Perfil do recém-nascido submetido à correção cirúrgica primária de gastrosquise: manejo nutricional e prognóstico pós-operatório - Flavia Miranda da Silva (2014)
Gastroschisis is a congenital malformation that requires surgery immediately after birth, and there are many complications related to early surgical intervention and hospital stay required. The main problems associated with gastroschisis are mainly due to intestinal dysfunction (obstruction, atresia, adhesions, resection, small bowel) and the length of hospital stay being associated with episodes of septicemia and malnutrition. In this study, neonates with gastroschisis submitted primary closure were identified and investigated their nutritional characteristics in relation to morbidity and mortality. A retrospective cohort study was conducted from January 1995 to December 2010, covering 16 years. Were selected 49 surgical primary repair patients. The variables were described in epidemiological way presenting in three groups: maternal variables, the newborn and nutritional variables. Then, analysis has been made considering correlation between these variables and their influence on mortality and morbidity in the newborn. The unique feature able influence mortality was the need for a second surgical intervention during hospitalization, an increase by 9.25 times the odds of death. Though, maternal characteristics, including prenatal variables, were not able to affect mortality. The characteristics that influenced morbidity were classification of neonate (weight / gestational age), use of antibiotics, days of life needed to start enteral nutrition and to achieve full diet. It is noteworthy that the classification of neonates as small for gestational age increased to 24.2% the length of hospital stay. Moreover, according to the time of introduction of the diet, it was found that neonates that there was delay in starting the diet increased to 2.1% the length of staying. However, achieving more slowly the full volume of diet acted as a protective factor decreasing by 3.6% the length of stay. Nevertheless, there were not significant correlation between the waste volume drained by gavage before the start of diet with morbidity even with the time of introduction the diet.